PKM Menulis Ekspresif untuk Menurunkan Trauma Penyintas Bencana Sulawesi Barat - Ahmad Ridfah; Sitti Murdiana (PENGABDI, 2022)
Abstract The partner of this Community Partnership Program (PKM) was a Desa Taan. The problem found was that the survivors of the earthquake were traumatized, thus disrupting their daily lives. The target of this program is earthquake survivors. The method used is that the survivors are asked to write expressively four times in a row, for four days. Survivors were asked to write about their thoughts, experiences, and feelings related to the earthquake they experienced. The final results showed that there were positive changes in the feelings, thoughts, and behaviors of the disaster survivors who participated in this programKeywords: earthquake disaster, expressive writing, survivor